A norma jurídica à luz da Semiótica de Peirce: um estudo de caso - Verginassi, Michelle Tavares [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The present study intends in a general and simple way, based on Peirce's Semiotic Theory, to demonstrate how it is possible to analyse and describe legal dispositives, here consisted of the articles of the Brazilian Forestal Code, trying to turn manifest the ambiguities, gaps, ideologies subsumed under the text. In order to proceed in this intent we will present Geradi's concept of Language, and passing by Jackobson's communicative model, we will arrive at the Juridical Language, trying to establish the inter-relational playing between Semiotic as a Metalanguage of Law, while Law plays the role of Object-Language. In the following step, the assumed standpoint will become clearer with our approach of Peirce's Semiotics, whose aim is the study of the essential aspects of every kind of phenomena productive of signification, here represented by Law. Finally, we will proceed to a study of case through the semiotic analysis and description of the interposed articles of the new Brazilian Forestal Code, 2012, that will demonstrate that such articles, depending of their material content, assume the above mentioned postures.

O presente estudo pretende demonstrar de modo geral e simplificado com base na teoria Semiótica de Peirce, como é possivel se analisar e descrever dispositivos legais, aqui propostos os artigos vetados do novo Código Florestal Brasileiro, buscando de certa forma trazer à luz suas ambiguidades, vaguezas, lacunas e ideologias subssumidas pelos textos. Para isso, abordamos o conceito de Linguagem proposto por Geraldi, passaremos pelo modelo comunicativo de Jackobson e adentraremos a Linguagem Jurídica, demosntrando o jogo inter-relacional da Semiótica como uma metalinguagem do Direito - sua Linguagem Objeto. Esta visão ficará mais clara logo em seguida, onde abarcaremos o estudo da Semiótica proposta por Peirce, que tem por objetivo o estudo dos apectos essenciais de todas as espécies de fenomenos produtor de significação, aqui o Direito; e por fim, traremos o estudo de caso com a análise e descrição semiótica dos artigos vetados do novo Código Florestal Brasileiro/2012, que nos demontrará como tais artigos, dependendo de seu conteúdo material, assumem as posturas supracitadas.
Keywords: Peirce, Charles S Charles Sanders 1839-1914; Linguagem - Filosofia; Semiotica; Semantica (Direito); Semantics (Law)